2019
DOI: 10.1111/bju.14666
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy for prostate cancer and risk of dementia

Abstract: ObjectivesTo study whether androgen deprivation therapy (ADT), the mainstay treatment for advanced and disseminated prostate cancer, is associated with risk of dementia. MethodsRisk of dementia in men with prostate cancer primarily managed with ADT or watchful waiting (WW) in the Prostate Cancer Database Sweden, PCBaSe, was compared with that in prostate cancer-free men, matched on birth year and county of residency. We used Cox regression to calculate the hazard ratios (HRs) for Alzheimer's and non-Alzheimer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Our analysis of the risk of AD death in cancer patients relative to reference populations, stratified by race, cancer sites, age at diagnosis and time since cancer diagnosis, suggests a decreased risk of AD death in white patients diagnosed with different solid tumors or leukemias at the age of ≥45 years. This agrees with previous studies which reported inverse associations between cancer and the risk of AD [53][54][55][56]. However, our work identified specific solid tumors and hematolymphopoietic malignancies associated with a decreased risk of AD death in white patients and demonstrated modification of this protective effect by both age at diagnosis and time since cancer diagnosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analysis of the risk of AD death in cancer patients relative to reference populations, stratified by race, cancer sites, age at diagnosis and time since cancer diagnosis, suggests a decreased risk of AD death in white patients diagnosed with different solid tumors or leukemias at the age of ≥45 years. This agrees with previous studies which reported inverse associations between cancer and the risk of AD [53][54][55][56]. However, our work identified specific solid tumors and hematolymphopoietic malignancies associated with a decreased risk of AD death in white patients and demonstrated modification of this protective effect by both age at diagnosis and time since cancer diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…The difference between the results of our study and those from the national veterans study for prostate cancer may stem from a possible difference between the prostate cancer cohorts in the use of androgen-deprivation therapy (ADT), which was found by some but not all investigators to increase the risk of AD [54]. Nevertheless, a recently reported Swedish study found an increased risk of dementia but not AD in prostate cancer patients treated with gonadotropin-releasing hormone agonists (HR = 1.15; CI95: 1.07-1.23) or orchiectomy (HR = 1.60; CI95: 1.32-1.93), and no increased risk for any type of dementia (of which, majority are usually due to AD) in men treated with oral antiandrogen or managed by watchful waiting [55], which is consistent with our results.…”
Section: Interpretations Of the Cancer-ad Association Datamentioning
confidence: 97%
“…ADT has also been associated with the development of dementia. In this regard, Robinson et al (2019), in a large cohort study, described a higher risk of non-Alzheimer dementia in PC patients exposed to ADT (Hazard Ratio=1.24 (95%CI: 1.14-1.36) [12]; Nguyen et al (2018) also described a higher risk of dementia in ADT users [7]; and Kim JH et al (2018), in a meta-analysis of seven studies, concluded that there is a positive association between the use of ADT and the incidence of dementia (including Alzheimer’s disease) [13]. Cognitive ADT-associated effects seem to appear, at least, after 6 months of treatment [14] and seem to be positively correlated with the ADT duration [15].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies on the association between ADT and dementia have reported the dementia risk according to ADT type. 9 , 37 Khosrow-Khavar et al 9 reported similar dementia risks of GnRH agonist or antiandrogen monotherapy compared with those who did not receive ADT. Notably, the overall incidence of dementia in their study (approximately 0.59 per 100 person-years) 9 was significantly lower than that reported by Baik et al 10 (3.27 per 100 person-years) and our study (1.76 per 100 person-years).…”
Section: Discussionmentioning
confidence: 98%